Effect of inhomogeneous dispersion shaping of a helical SWS on the backward-wave oscillation criterion - Seshadri R.; Raja Ramana Rao P.; Rao K.V.; Datta S.K.; Kamath S.; Jain P.K. (My University, 2025)
The effect of inhomogeneous dispersion shaping of a helical SWS on the backward-wave has been studied. Theoretical simulations of three types of dispersion, namely, positive, flat and negative, achieved in an inhomogeneous structure and the interaction impedance characteristics thereof were carried out. The analysis of backward-wave oscillation criterion has been carried out to assess the effects of dispersion shaping and the beam-filling factor. A negative dispersion structure has been found to be advantageous in improving the threshold for backward wave oscillation.